Strategi Bertahan Subak di Daerah Pariwisata (Kasus Subak Semujan, Kecamatan Ubud, Kabupaten Gianyar) - I GUSTI NGURAH BAGUS SUPARDI PUTRA; I KETUT SURYA DIARTA; WAYAN SUDARTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Survival Strategies of Subak in the Tourism Area (in the Case of Subak of Semujan, Subdistrict of Ubud, Regency of Gianyar) Subak Semujan is a subak located in Ubud tourism center, now it is threatened by tourism itself. From 2012 to 2016 Subak Semujan has undergone land conversion of 15 hectares. This decrease is due to the conversion of agricultural land into tourism facilities such as hotels, bungalows, restaurants, and villas. The purpose of this research is to design the survival strategies of Subak of Semujan in the tourism area. Result of internal factor analysis Subak Semujan: a) strength: religious ceremony, awig-awig and pararem (traditional customs and rules), b) weakness: lack of interest of the farmers' children in the agricultural field, adopting lower innovation or technology. External factors: a) opportunities: social assistance and rice production facilities, farming extension, b) threats: tourism businesses require agricultural land, tourism employment opportunities. Based on the SWOT analysis, survival strategies are: a) S-O strategy of agricultural extension activities to be able to maintain agriculture in tourism area and to promote farming activities in the form of tour packages, b) S-T strategy: to make special rules related to land conversion and irrigation channel (awig- awig), c) W-O strategy: education and training through extension in adopting new innovations, agricultural extension for the younger generation, d) W-T Strategy: giving material and non-material incentives to the members of subak.